"Bullwhip Effect" in Supply Chains - Anđelko Ščukanec; Kristijan Rogić; Darko Babić (Promet (Zagreb), 2007)
The system which connects all the elements between theproducer and the consumer is called the supply chain. This definitionof the supply chain shows its complexity, dynamics anduncertainty. Successful operation of supply chains requires thebest possible coordination of its elements, which obviously indicatesthe utmost importance of the information flow alongthem. The operation of supply chains on the whole has to bemore successful than the operation of their individual elements.It should be noted that such a complex process may give rise toa series of problems, unwanted events, as well as substantial reductionin profits and the level of service. One of such unwantedphenomena which may occur in the supply chain is the"bullwhip effect". This is a possible increase in the diversity oforders which occurs when we move along the elements of thesupply chain (from the customers' orders to the producers' orders).The work analyses the processes within the supply chainsand the occurrence of the bullwhip effect. The main causes ofthe bullwhip effect that we encounter daily in the supply chainshave been clearly defined. The paper also presents the mainnegative consequences of such a disturbance within the supplychains, and provides possible solutions for avoiding the bullwhipeffect.